2015
DOI: 10.7860/jcdr/2015/13254.6071
|View full text |Cite
|
Sign up to set email alerts
|

Ewing’s Sarcoma Multifocal Metastases to Temporal and Occipital Bone: A Rare Presentation

Abstract: An 11-year-old male patient was referred to the ENT department at Lok Nayak Hospital with the complaints of right ear discharge, facial weakness, inability to close right eye, and a gradually progressive occipital swelling for one month. In addition, he complained of decreased hearing from right ear, as well as headache. The patient was a known case of Ewing's sarcoma of the left pelvic bones, with involvement of iliac bone, ischium and sacroiliac joint. He had presented initially with the complaints of pain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In the literature, headache, localized swelling, and signs of raised intracranial pressure were the most common symptoms of skull ES 1,3,5,6,7,9 , this could be explained as they found that, the Intracranial extension was present in the majority of primary cases of the skull ES 4 . The main presentation of ES in the temporal bone was facial paralysis, hearing loss and ear discharge 5,7 . Even though it may differ from case to case depending on the location and spread of the tumor, but some researchers did not find significant difference in the presentation of primary and metastatic tumors 5 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In the literature, headache, localized swelling, and signs of raised intracranial pressure were the most common symptoms of skull ES 1,3,5,6,7,9 , this could be explained as they found that, the Intracranial extension was present in the majority of primary cases of the skull ES 4 . The main presentation of ES in the temporal bone was facial paralysis, hearing loss and ear discharge 5,7 . Even though it may differ from case to case depending on the location and spread of the tumor, but some researchers did not find significant difference in the presentation of primary and metastatic tumors 5 .…”
Section: Discussionmentioning
confidence: 98%
“…ES is the second most common malignant bone tumor in young patients 3,4,5 even though it accounts for only 1% of all childhood cancers 8 . Primary ES is more likely to affect long bones, pelvic bones, ribs, and vertebrae 1,2,5,6,7,8 presented most commonly in the second decade of life 2,3,4,5,7 with a male to female ratio of 1.6:1 1,3,5,7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations